Effective numerical integration of traveling wave model for edge‐emitting broad‐area semiconductor lasers and amplifiers - Čiegis, Raimondas; Radziunas, Mindaugas (Mathematical Modelling and Analysis, 2010)
We consider a system of 1 + 2 dimensional partial differential equations which describes dynamics of edge‐emitting broad area semiconductor lasers and amplifiers. The given problem is defined on the unbounded domain. After truncating this domain and defining an auxiliary 1 + 1 dimensional linear Schrodinger problem supplemented with different artificial boundary conditions, we propose an effective strategy allowing to get a solution of the full problem with a satisfactory precision in a reasonable time. For further speed up of the numerical integration, we develop a parallel version of the algorithm. First published online: 10 Feb 2011